Photosensitized dimerization in pyrimidine-based thin solid films - Patra, A.; Ralston, J.; Sedev, Rossen; Zhou, J. (Elsevier S.A., 2011)
Thin solid films of thymine and uracil derivatives, incorporating a photosensitizer in the film, were prepared on quartz surfaces using a dip-coating technique. Photosensitized dimerization in these thin solid films was investigated in this study and compared with the conventional, non-photosensitized reaction. Both carbonyl and p-aminobenzoic compounds were selected as photosensitizers. It was found that only p-aminobenzoic compounds such as p-aminobenzoic acid and N-dodecyl p-aminobenzoic acid were effective in causing the photosensitized dimerization of thymine, upon exposure to light of wavelength 313 nm. Uracil surfaces, however, do not photodimerize under these conditions. The concentration of photosensitizer and the solvent selected in the dip-coating process strongly influenced the dimerization process. The reaction rate of sensitized dimerization follows a pseudo-first order reaction.